Stakeholders’ Expectations of Graduates of a Work-Study Nursing Upskilling Programme in East Africa - Brownie, Sharon; Mwizerwa, Joseph; Gatimu, Samwel Maina; Kambo, Isabel (Africa Journal of Nursing and Midwifery, 2020)
Sound alignment of stakeholders' expectations and graduate ability forms the reputational hallmark of a university's education programmes. However, little is currently known about stakeholders' expectations of graduates of work-study nursing upskilling programmes in low- and middle-income settings. Information is needed to ensure the quality and adequacy of curricula in such settings. The main aim of the current study was to explore the nursing stakeholders' expectations of graduates of work-study nursing upskilling programmes. An exploratory qualitative study was conducted between March and October 2016 in three low- and middle-income countries in East Africa. Forty-two representatives of nursing employers, regulators and professional associations (PAs) participated. The data was collected during 27 key informant interviews (KIIs) and three focus group discussions (FGDs) using a pretested interview guide. Content analysis of the data was completed. Consolidated criteria for reporting of qualitative research guidelines were used as the standard for collecting data and reporting results. Stakeholders reported their expectations of a clinically and professionally competent nurse (an “all-round” graduate) with nursing management and leadership skills that facilitated sound clinical judgement and decision making and a high level of professionalism. The study highlighted nursing stakeholders’ expectations of nursing graduates who had completed a work-study upskilling programme. These expectations should inform curriculum planning and development, and highlight the need for a strong focus on clinical competence, leadership, critical thinking and professionalism in nursing upskilling programmes.